Forced returns and fragile lives: strategies for safeguarding Syrian refugees and ensuring their protection - Elshobake, Mohammed R. M.; Sakka, Alaa (Brill Academic Publishers, 2025)
The article discusses the deportation of Syrian refugees from Lebanon and Turkey between 2017 and 2024. It attempts to bring light on the experiences of these refugees facing forced returns, emphasising the human consequences and complicated causes underlying such actions. The purpose of this article is to raise awareness about the deportation of Syrian refugees and the urgent need for collective action to address this humanitarian disaster and preserve the lives of vulnerable individuals affected by forced repatriation. Using the descriptive analytical approach, this article investigates the legislative frameworks and international commitments that should safeguard refugees from forced repatriation. The Universal Declaration of Human Rights (UDHR), The 1951 Convention Relating to the Status of Refugees and its 1967 Protocol and rules of International Humanitarian Law will be used as a standard for the definition and legal framework of refugee’s rights. The article dives into the obstacles that host countries confront, including as social, economic, and political pressures. It also emphasises the necessity of advocacy activities and protective measures to defend Syrian refugees’ rights and well-being. The findings of the article are expected to benefit Syrian refugees and raise awareness about their situation, which will contribute preserve their lives and well-being.